Correction: Enhanced endocytosis of acid-sensitive doxorubicin derivatives with intelligent nanogel for improved security and efficacy. (1st December 2014) - Ding, Jianxun; Shi, Fenghua; Li, Di; Chen, Li; Zhuang, Xiuli; Chen, Xuesi
Abstract : Correction for 'Enhanced endocytosis of acid-sensitive doxorubicin derivatives with intelligent nanogel for improved security and efficacy' by Jianxun Ding et al., Biomater. Sci., 2013, 1, 633–646.